Empowerment of Plant and Livestock Integrated Farmer Groups Based on Digital Marketing and Finance: Pemberdayaan Kelompok Tani Terintegrasi Tanaman dan Ternak Berbasis Pemasaran dan Keuangan Digital - Eka Yulianti; Dwi Indah Lestari; Henly Yulina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The city of Bandung has partners who have contributed to the community's food security. One of the partners is the Bestari Farmer Group, which is located in a densely populated area and has the potential to develop. However, partners have problems including, 1). The product is not yet known to the market. 2). There is no attractive packaging. 3). Bookkeeping and financial reporting have not been managed properly. 4). Do not have regular planting and harvesting schedules. 5). lack of knowledge related to greenhouses and hydroponics 6). Management of chicken livestock is less than optimal. 7). The management of catfish livestock is less than optimal. Therefore, the purpose of this community service is to increase the ability and knowledge of partners to be able to market their products and assist in increasing productivity with optimal financial bookkeeping. The methods in this program are training, practice, mentoring, focus group discussions, and evaluation. The results show that seven programs have been implemented that are solutions to the identified problems. Partners are ultimately able to understand and carry out digital-based financial and marketing records and increase the productivity of farming and livestock businesses.